Business Planning : Art Solution / Muhammad Fariz Mohad Azmi...[et al.] - Mohad Azmi, Muhammad; Abd Hamid, Saidatul Najihah; Muda, Muhammad Shafiq; Nazeron, Izad Shaharul; Syed Mazlan, Sharifah Nadia; Mohd Nor, Nur Munira (2008)
UiTM student expecially art and design student specialist in fine metel tools . Thus, our business has been creat because to resoulve a problem to the student to get their equipment in expecially for UiTM art and design student because some time the equipment that they want to use is difficult to get in the area of Machang and the nearest place to get all the equipment is in Kota Bharu. We confident to managed and compete this business bacause our partners want to rasolve to a UiTM student. Our mission is to give the solution to a art and design student to get their equipment and give the best to our own company